DOES CARE BURDEN OF DEMENTIA VARY BY LOCOMOTIVE FUNCTION AMONG JAPANESE ELDERLY PEOPLE?. (16th November 2018) - Jinnouchi, H; Tamiya, N; Ueshima, H; Kawada, T; Ishizaki, T; Yoshie, S; Iijima, K
Abstract: The aim of this study was to analyze the impact of dementia with differential levels of locomotive function on heavier care burden. A cross-sectional study was conducted to analyze 10, 150 persons aged 65 years or older (male, 33.6%) with officially certified care necessity during April 2009 and March 2014 in a suburban city in Japan. Heavier care burden was defined as estimated duration of daily care requirement 70 minutes or longer. Dementia was judged based on the standardized physicians' classification II or greater, which was validated by a comparison with neuropsychiatrists' diagnoses defined by the International Psychogeriatric Association. Locomotive function of each study participant was evaluated based on one's ability to stand-up, walk, sit, and roll over on a bed. Those high discrimination abilities were confirmed by item-response theory analyses, and we could divide their mobility into four categories: higher, high, low, and lower. The proportion of dementia among persons who were certified care necessity was 30.3%. Using logistic regression analyses with stratified by the locomotive function group, calculated sex- and age-adjusted odds ratios of dementia for heavier care burden in higher, high, low, and lower mobility group were 9.4 (95% confidential intervals: 6.2–14.0), 5.3 (3.8–7.5), 4.1 (3.5–4.7), 8.5 (5.8–12.4), respectively, compared to no dementia. Heavy care burden of dementia, which requires communicational assistance more than physical assistance generally, was observed among the elderly with physically independent as well as bed-bound with/without high medical needs.